Effect of laundry detergent formulation on the performance of alkaline phytoproteases - Barberis, Sonia (2013)
Background: Proteases constitute the largest product segment in the global industrial enzymes market; they are used in food, pharmaceutical, leather, textile, wood and detergent industries. Alkaline proteases improve the cleaning efficiency of detergents and represent one of the most successful applications of modern industrial biotechnology. The aim of this work was to study the performance of two alkaline phytoproteases, araujiain (Araujia hortorum Fourn.) and asclepain (Asclepias curassavica L.), for their potential application as additive in laundry detergent formulations. Results: The effect of pure non-ionic and ionic surfactants on proteolytic activity of araujiain and asclepain was analyzed measuring the remaining activity after 1 hr of incubation of those enzymes in aqueous solutions of surfactants at different concentrations (0.1, 0.4 and 1% v/v) and temperatures (25, 40 and 60oC). Besides, the compatibility of the enzymes with six commercial laundry detergents was also studied measuring the remaining proteolytic activity at 37oC after 1 hr. Commercial detergent components influenced in different ways on araujiain and asclepain, in spite of the similar behaviour of the two enzymes in buffer. In commercial detergent solutions, araujiain expressed between 60% and 140% of its remaining proteolytic activity in buffer (pH 8.5) at 37oC after 1 hr, while asclepain, was practically inactivate in most of them at the same conditions. Conclusions: Proteolytic extract of Araujia hortorum fulfilled all the requirements for its application as additive for laundry detergents: high stability in a broad temperature range (25-70oC), high activity in alkaline pH (7.5-9.5) and very good compatibility with the commercial detergent additives. Nevertheless, in spite of its high stability and activity in buffer, the proteolytic extract of Asclepias curassavica did not show the same performance than araujiain.